Metode Pembaruan Hukum Keluarga Muslim - Nasihatul Fadillah; Lilik Andar Yuni (Bulletin of Community Engagement, 2024)
Islamic family law is a field of legal studies that is largely applied in Muslim countries today. Generally, the implementation of these laws takes the form of formal state legislation. Muslim countries from the Middle East, North Africa, South Asia to Southeast Asia almost all have family law legislation. This indicates that family law is a very important field of Islamic law as it is implemented evenly in the contemporary Islamic world. Muslim countries continue to strive for reforms and changes in family law legislation to address emerging issues in line with the times. This research aims to present the models of reform and the methods used by Muslim scholars or intellectuals in the reform of Islamic law in Muslim countries. The method used is a qualitative data approach as it is library research. This research found that there are three models of Islamic family law reform: 1) countries that do not undertake reforms, 2) countries that abandon conventional fiqh concepts and shift to liberal concepts, 3) countries that undertake moderate reforms in accordance with changing times. The methods used in these legal reforms are twofold: 1) Intra-doctrinal reform through takhayyur and talfiq, 2) Extra-doctrinal reform through maslahah mursalah, sadd al-dhari’ah, regulatory, siyasah syar’iyyah (administration), and court decisions.